BRAND MANAGEMENT THROUGH THE LENS OF KNOWLEDGE: A STUDY OF BRAND CHOICE OF LAPTOPS BY MANAGEMENT STUDENTS - Vikas Nath and S.Goswami (Abhigyan, 2010)
Brands have value and varying values underlie the brand's importance in the marketplace. Brand stands on its values, salience, identity, leverage and above all, personality or equity. Consumers usually would like to buy a brand having goodwill in the market, which should be seen as trust worthy and matching their life style where values creep in. While a whole industry has grown up around the need to promote and build brands, it can be argued that brand image/ identity is no substitute for brand reality. No one can dispute the power of a brand. Brands give reliance to trust, reassurance of quality and increasingly, status. Thus, in many advertisements the number of existing customers is a good strategy to communicate with the customers. This will not only make the brand distinct but will also create a feeling of trust worthiness among the potential and existing consumers. Brand value, in essence, will represent the service and behaviour that is expected from the brand. There is little doubt that the most successful brands of laptops for example, historically have communicated and delivered a high level of consistency.